Performance Evaluation of Backside Emitting O-Band Grating Couplers for 100- $μ$ m-Thick Silicon Photonics Interposers - Nivesh Mangal; Jeroen Missinne; Geert Van Steenberge; Joris Van Campenhout; Bradley Snyder (IEEE Photonics Journal, 2019)
Most of the single-mode fiber-coupled grating couplers reported in the literature have been designed for upward directionality to perform wafer-scale testing of photonic-integrated circuits. A coupler designed for downward directionality can help in achieving a face-up electro-optic integration scheme for chip-to-board coupling using 2.5-D/3-D silicon photonics interposers. We demonstrate for the first time the design analysis and coupling performance of TE-polarized O-band through-substrate (backside emitting) grating couplers that have been optimized to produce enhanced directionality in the downward direction into the bulk silicon substrate of a Si photonics chip. The chip substrate was thinned and polished to achieve a bulk silicon thickness of 100 $μ$ m. By the use of an optimized reflector and an optimal thickness of anti-reflection coating at the backside of the chip, a $-$ 2.3 and $-$ 1.7 dB fiber-to-grating coupling efficiency has been measured when coupled through-substrate to a single-mode and multimode fiber, respectively. These gratings with downward directionality can help provide an efficient and alignment-tolerant interface for chip-to-chip or chip-to-board optical interconnects.